THE INFLUENCE OF SUPERVISOR PHUBBING ON COMMUNICATION SATISFACTION, TRUST AND EMPLOYEE PERFORMANCE: (Correlation Study on State Civil Apparatus At The Regional Secretariat Of North Tapanuli Regency) - Reinhard Pasaribu, Tupa Baen (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to analyze the effect of supervisor phubbing on employee communication satisfaction with supervisor, employee trust in supervisor and employee performance at the Regional Secretariat of North Tapanuli Regency. A quantitative approach with an explanatory method was used in this study. The theories used in this study are Expectancy Violation Theory, Media Dependence Theory and Social Presence Theory. The population in this study were all ASN at the Regional Secretariat of North Tapanuli Regency who have Functional Positions (staff). The sampling technique in this study used the total sampling technique. The research instrument was distributed to 105 research respondents through a questionnaire. The research data were analyzed using a single table analysis, direct effect test and indirect effect test. The results of the study tested using the SmartPLS application showed that supervisor phubbing had a significant negative effect on subordinate communication satisfaction with supervisor. Supervisor phubbing had a significant negative effect on employee trust in supervisor. Supervisor phubbing had a negative and significant effect on employee performance.